2014
DOI: 10.3109/10717544.2014.977460
|View full text |Cite
|
Sign up to set email alerts
|

Development, optimization and characterization of glycyrrhetinic acid–chitosan nanoparticles of atorvastatin for liver targeting

Abstract: Glycyrrhetinic acid-modified chitosan (mGA-suc-CTS) is used as liver-targeted carrier for drug delivery. In this study, nanoparticles were prepared by ionic gelation process, and glycyrrhetinic acid act as the targeting ligand. The structure of the product was confirmed by IR and NMR techniques. The main aim of this study was to deliver atorvastatin directly to the liver by using same conjugate and reduce the associated side-effects, i.e. hepatotoxicity at high dose. Characterization of the developed formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…20 The particle sizes of ATV-LNE ranged from 38.12±6.71 to 119.2±16.17nm which was similar to the results observed by Kumar who reported the particle size of ATV loaded solid lipid nanoparticles was ranged from 50.0±4.12 to 125.1±6.12 nm. 21 The particle size of 20% ATV-LNE has the smallest size with z-average diameter of 38.12±6.71nm and has the largest zeta negative potential of -26.8±4.16mV.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…20 The particle sizes of ATV-LNE ranged from 38.12±6.71 to 119.2±16.17nm which was similar to the results observed by Kumar who reported the particle size of ATV loaded solid lipid nanoparticles was ranged from 50.0±4.12 to 125.1±6.12 nm. 21 The particle size of 20% ATV-LNE has the smallest size with z-average diameter of 38.12±6.71nm and has the largest zeta negative potential of -26.8±4.16mV.…”
Section: Discussionsupporting
confidence: 79%
“…23 this was in agreement with Rohilla et al who found the PDI of ATV loaded in glycyrrhetinic acid-chitosan nanoparticles was 0.126. 20 When investigating the lipid profile, it was noticed that the cholesterol and LDL levels were decreased in all treated groups slightly. 20% ATV-LNE and Blank-NE groups have the least level of CHO and LDL compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between HA-adh-DOCA 10 and HAadh-GA 20 micelles was ascribed to the different hydrophobic moiety. Studies have described that GA-modified drug delivery systems accumulated particularly in the rat liver and maintained at a high level, because of the abundant receptors for GA on hepatocyte membranes Rohilla et al, 2014). In this study, although most of the hydrophobic GA molecules were embedded in the inner core of micelles, some GA molecules were still present on the surface of HA-adh-GA 20 micelles, serving as liver-targeting ligands.…”
Section: In Vivo Imaging Analysismentioning
confidence: 76%
“…The risk of transmission of the disease is high because the infection has been detected in nonendemic areas of the Americas and Europe due to largescale migrations. It is essential to develop new strategies for the prevention and control of Chagas disease (Rohilla et al, 2014a). At present, vaccines and immune therapies targeted at T. cruzi infection are practically nonexistent.…”
Section: Immunoadjuvant For a Vaccine Against Chagas Diseasementioning
confidence: 99%